AWARENESS AND PERCEPTION OF INTERNET FRAUD EPIDEMICS AMONG NIGERIAN YOUTHS - Eke, Chigozi (African Journal of Social and Behavioural Sciences, 2024)
The surge in internet fraud poses a critical challenge among Nigerian youths, requiring heightened awareness and an accurate understanding of the issue. This alarming trend raises concerns about the level of awareness and perception of internet fraud. Understanding the factors that contribute to this epidemic and the youths’ perceptions of it is crucial for developing effective preventive measures and safeguarding their online experiences. This study examined the awareness and perception of internet fraud among Nigerian youths. The theoretical framework Media technological determinism and technology-enabled crime theories underpinned the study as a theoretical framework. The study adopted a descriptive research design. The population of the study consisted of all Nigerian youths, all young people between the ages of 18 and 35 years who are citizens of the Federal Republic of Nigeria. The population for the study included 3,599,589 youths from the state capital of the geopolitical zone, Nigeria. The sample size was 384 according to Keyton’s sampling determinant formula. The study adopted multistage cluster sampling techniques. A questionnaire was used for data collection and, percentages and weighted mean scores (WMSs) were used for data presentation. The findings of the study revealed that the level of awareness of the epidemic of internet fraud was very high and that there were more people associated with internet fraud among young people. The study recommended that, because the level of awareness of the epidemic of internet fraud is high, a massive awareness campaign should be undertaken to educate youths in Nigeria about the knowledge on the consequences of internet fraud.